2020
DOI: 10.1109/access.2020.2987807
|View full text |Cite
|
Sign up to set email alerts
|

A Robotic Grinding Motion Planning Methodology for a Novel Automatic Seam Bead Grinding Robot Manipulator

Abstract: Industrial robotics is a continuously developing area of in-depth robotics research, as industrial robots have demonstrated to possess advantages in the robotic automation solutions in the industrial automation applications. In this paper, a novel automatic seam bead grinding robot manipulator with the integration of machining and measuring is proposed and an experimentation platform is developed for the robotic removal of the seam weld beads at welded pipe ends. Also, a robotic grinding motion planning method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Ge et al used robots and line laser sensors to realize the welding seam of the steel pipe workpiece via online measurement and removal [14]. Guo et al used robots and line laser sensors to measure and remove spiral welds on steel pipes [15]. Among them, it can be found that due to its limited accuracy, 3D cameras are often used in applications where precision requirements such as deburring and polishing are not high.…”
Section: Related Workmentioning
confidence: 99%
“…Ge et al used robots and line laser sensors to realize the welding seam of the steel pipe workpiece via online measurement and removal [14]. Guo et al used robots and line laser sensors to measure and remove spiral welds on steel pipes [15]. Among them, it can be found that due to its limited accuracy, 3D cameras are often used in applications where precision requirements such as deburring and polishing are not high.…”
Section: Related Workmentioning
confidence: 99%
“…Traditional manual grinding not only has uneven grinding quality and low efficiency but also generates dust during the grinding process, which is hazardous to workers' physical and mental health. In contrast, robotic grinding can replace manual grinding and achieve automation [1]. Maintaining a constant grinding force during robotic grinding not only ensures the accuracy and consistency of the surface quality of the workpiece but also reduces the wear and tear on the robot and end-effector [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, robot manipulators have been widely used in many fields, such as manufacturing [ 1 ], assembly [ 2 ], grinding [ 3 ], and drilling [ 4 ]. However, these robotic arms are almost always mounted on fixed bases, significantly limiting their working space.…”
Section: Introductionmentioning
confidence: 99%